Chronic Lower Back Pain and Its Relationship with Vibration Exposure and Sitting Duration; A Cross-Sectional Study Among Commercial Motorcycle Driver - Bernath Siagian; Ambar W Roestam; Dewi S Soemarko; Sudadi Hirawan; Indah S Widyahening; Suryo Wibowo (The Indonesian Journal of Community and Occupational Medicine, 2022)
Background: Lower back pain (LBP) complaints are a health issue that may lead to restrictions on work activities. Motorcycles vibrations and long sitting duration on the motorcycles can cause chronic lower back pain complaints. Base motorcycles drivers receive motorcycles vibration exposure while riding a motorcycle. With the large number of base motorcycles drivers in Indonesia, the specific health problems (LBP complaints) in this group need to be examined.Methods: This research method uses a cross sectional study design to examine the relationship of motor vibration exposure and length of sitting to chronic low back pain with sampling technique used is Consecutive sampling. Consecutive sampling is a way of taking samples by selecting samples that meet the inclusion criteria until a certain time period so that the number of samples is met. The sampling period in this study is 2 days. The variables that measured were chronic lower back pain complaints, vibration, long sitting time, age, IMT, smoking, and working time. Data analysis using SPSS Statistics version 25.0. Results: A total of 95 subjects were included in this study. Based on Fisher’s test, the result of the correlation of chronic lower back pain complaints with motor vibrations > 0.5 m/s2 was obtained p = 0.102; OR = N / A). While for long sitting time of >4 hours result in p = 0.717; OR 0.85; CI 95% = 0.34-2.09. There is no difference in age-related chronic lower back pain complaints. At age> 35 years of age p = 0.722; OR 1.57; CI 95% = 0.31-7,9. No significant association between IMT and chronic lower back pain was found. In the IMT group> 25, p = 0.103 was obtained; OR 2.14; 95% CI = 0.85-5.36. There was no significant difference in chronic lower back pain complaints based on smoking status, where smoking group had p = 0.451; OR 1,45; CI 95% = 0.55-3.78. According to the Fisher test, there was no difference in chronic lower back pain complaints based on working age, where groups with> 4 years of work had a p = 0.908 value; OR 1.07; CI 95% = 0.31-3.91. Conclusion: In this study the hypothesis was rejected. There is no association between motorcycles vibration exposure and the occurrence of chronic lower back pain complaints in the base motorcycles driver in Bekasi city. There is no association long sitting time with the occurrence of chronic lower back pain complaints in the base motorcycles driver in Bekasi city.